La red pre asociación de productoras agropecuarias Ayora - Cayambe (Agropaga) : Vínculos sociales, económicos y ecológicos que se tejen en su interior - Chicaiza Valenzuela, Patricia Verónica (2015)
This research describes the food production, processing, marketing and process of empowerment of rural women that are part of AGROPACA, a pre-association, dedicated to agroecological production. This thesis deals with the problem of limited reflection, in Ecuador, on the links between agroecology, empowerment of women and food networks. This conceptual blindness, which is not unique to Ecuador, has an effect on the valuation of women´s work within the family and, especially, their impact on state policies. Given this problem, the question posed in this research is: How does the work in the "Pre- Association of producers and Cayambe Ayora" (AGROPACA) has influenced the empowerment of women (AGROPACA)? Consequently, the main objective of this dissertation is to explain the work of the Association AGROPACA as agroecological producers, the empowerment processes of their members and the links created during this work. The research is qualitative. It consists of a case study of AGROPACA association. The study group was AGROPACA constructed for five groups and made up of thirty-two families. Through methods such as participant observation, semi-structured interviews, in-depth interviews with key informants such as managers, technicians, coordinators of groups, producers and consumers. This thesis concludes that the AGROPACA Association, and their members, works as an agroecological food network where, thanks to the generation of (environmental, social and economic) ties, women have got empowerment.